Ethnomedicinal plant employment by the Buket ethnic in Sarawak, Borneo - Abu Bakar, Fauziah; Ismail, Zahora; Magiman, Mohamad Maulana; Chai Chin Fern, Elena Gregoria (African Science Publications, 2024)
Ethnopharmacological relevance: Sarawak, also known as the ‘Land of the Hornbills’, is culturally diverse. The region houses numerous ethnic groups with unique traditions, languages, and customs. Buket, an ethnic minority in Sarawak, is renowned for employing medicinal plants as a key component of its primary healthcare system. Nevertheless, regular medicinal plant traditional knowledge updates are necessary to preserve indigenous wisdom from being lost due to urbanisation. Aim of the study: The study aims to assess and document the ethnomedicinal knowledge of the Buket tribe, which encompasses traditionally utilised medicinal plant species, preparation methods, and plant parts. The current study also focuses on the comprehension of the indigenous community regarding the identified medicinal plant applications. Materials and methods: The present study gathered data through comprehensive household surveys, in-depth interviews with respondents, focus group discussions, and field observations involving 35 respondents. Subsequently, the information was interpreted through use value (UV) and fidelity level (FL). Results: Following a thorough assessment, only 35 individuals were deemed knowledgeable and implemented traditional medicine. Most respondents (80%) were elderly and did not receive education. The results also demonstrated that 30 medicinal plants available in the study area were employed to treat several ailments. The plants from the Solanaceae were employed the most as medicinal resources, followed by the Fabaceae family. The Buket tribe primarily utilises leaves to prepare medicine, while the shoots, stems, fruits, and roots were not commonly employed. The respondents also reported that the herbal preparations were mostly administered orally and topically. Although the community predominantly prepare decoctions, they also directly ingest the plant components. The Buket tribe employs several medicinal plants in treating various illnesses, including fever, gastrointestinal disorders, hypertension, migraines, abdominal pain, and muscle discomfort. Orthosiphon stamenius, Tradescantia chrysophylla, Kalanchoe pinnata, and Plantago asiatica L. recorded the most significant UV at 0.94. On the other hand, Curcuma zedoaria Roscoe, Dyera costulata, and Tradescantia chrysophylla, revealed the highest FL for treating diabetes (97.1%), chicken pox (94.3%), and fever (91.4%), respectively. The findings offer a concise overview of the genus, species, and respective applications of the medicinal plants. Conclusion: The residents of the Uma Ukit village demonstrated a sound understanding of the medical properties of the medicinal plants growing in the study area. The villagers have also been using the plants for generations. The present study findings could significantly assist in preserving the importance of traditional knowledge, hence preventing its loss.